Quality indicators: completeness, validity and timeliness of cancer registry data contributing to the European Cancer Information System - Giusti, Francesco; Martos, Carmen; Negrão Carvalho, Raquel; Van Eycken, Liesbet; Visser, Otto; Bettio, Manola (Frontiers in Oncology, 2023)
Population-based Cancer Registries (PBCRs) are tasked with collecting high-quality data, important for monitoring cancer burden and its trends, planning and evaluating cancer control activities, clinical and epidemiological research and development of health policies. The main indicators to measure data quality are validity, completeness, comparability and timeliness. The aim of this article is to evaluate the quality of PBCRs data collected in the first ENCR-JRC data call, dated 2015.Methods: All malignant tumours, except skin non-melanoma, and in situ and uncertain behaviour of bladder were obtained from 130 European general PBCRs for patients older than 19 years. Proportion of cases with death certificate only (DCO%), proportion of cases with unknown primary site (PSU%), proportion of microscopically verified cases (MV%), mortality to incidence (M:I) ratio, proportion of cases with unspecified morphology (UM%) and the median of the difference between the registration date and the incidence date were computed by sex, age group, cancer site, period and PBCR.Results: A total of 28,776,562 cases from 130 PBCRs, operating in 30 European countries were included in the analysis. The quality of incidence data reported by PBCRs has been improving across the study period. Data quality is worse for the oldest age groups and for cancer sites with poor survival. No differences were found between males and females. High variability in data quality was detected across European PBCRs.Conclusion: the results reported in this paper are to be interpreted as the baseline for monitoring PBCRs data quality indicators in Europe along time.